Correlation Between Noise Levels and Noise-Induced Hearing Loss in Ground Handling Officers at Kualanamu Airport - Putra, Aldi Maulana; Herwanto, Yusa; Lubis, Yuliani M.; Ashar, Taufik (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Airport ground handling officers are highly exposed to noise from aircraft operations, potentially leading to Noise-Induced Hearing Loss (NIHL). This study aims to investigate the correlation between noise levels and NIHL among ground handling officers at Kualanamu Airport. A cross-sectional observational design was applied. Data on noise levels were obtained using a sound level meter, and NIHL was assessed with a calibrated Interacoustics audiometer AD528. Among 23 officers exposed to 95 dB, 16 (69.6%) had NIHL, and among 5 officers exposed to 100 dB, 4 (80%) had NIHL. Statistical analysis using the Kruskal-Wallis test confirmed a significant relationship between noise levels and NIHL (p<0.001). The study highlights the need for preventive strategies in noisy airport environments. The conclusion is that there is a significant correlation between occupational noise exposure and the incidence of Noise Induced Hearing Loss (NIHL) among ground handling officers at Kualanamu International Airport.